Analysis of the Impact of ICT for the Management and Control of Public Transport: A Review of Scientific Literature from 2015 - 2020 - Cabanillas-Carbonell, Michael (2021)
Management and control are fundamental processes for an efficient public transport. Processes can be improved through ICT support as this would help to increase productivity and to improve control inside a public transport company so much for the management and control of human resources, as well as the control of the vehicle fleet. This research is a systematic review of scientific literature. It aims to determine the different tools and strategies for control and management in public transport; it systematized 50 scientific articles extracted from the Scopus, Scielo, IEEE Xplore, Redalyc and ScienceDirect databases identifying the most relevant characteristics of ICT as well as the impact on the management and control in public transport.